Pengaruh Pengeluaran Pemerintah, Upah, Inflasi, Pendidikan dan Pengangguran terhadap Perekonomian dan Dampaknya terhadap Kemiskinan di Kawasan Teluk Tomini - Iren Syahrein Paris; Syarwani Canon; Sri Indriyani S. Dai (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effect of government expenditure, wages, inflation, education, and unemployment on the economy and their impact on poverty in the Tomini Bay Region. The study uses panel data from 10 regencies/cities with secondary data obtained from the Central Bureau of Statistics (BPS). The analytical method employed is a simultaneous equation model. The results show that government expenditure and education have a positive and significant effect on the economy. Wages have a negative and insignificant effect, while inflation and unemployment have a positive but insignificant effect on the economy. The economy has a positive and significant effect on poverty, indicating that economic growth has not yet been inclusive. Wages have a negative and significant effect on poverty, whereas inflation and unemployment have a negative but insignificant effect. These findings indicate that economic growth has not been fully capable of reducing poverty evenly, therefore policies focusing on equitable social welfare are needed.